Food security and nutrition in an urbanizing world: A synthesis of the 2017 Global Food Policy Report - Fan, Shenggen; Cho, Emily EunYoung; Rue, Christopher (Emerald Publishing Limited, 2017)
The paper is a synthesis of the 2017 Global Food Policy Report, and the purpose of this paper is to put into perspective the major food policy issues, developments, and decisions of 2016 and highlights challenges and opportunities for 2017.The paper presents an overview of recent changes in the global context for food security and nutrition, and synthesizes research findings on major issues that arise in an urbanizing world. Based on its findings, the authors present policy recommendations and areas for future research for food security and nutrition.Urbanization is linked with dietary changes to more energy-dense diets, and, the triple burden of malnutrition is increasing, particularly in rapidly urbanizing developing countries. Rural-urban linkages are key to improving food security and nutrition in both rural and urban areas, and traditional agricultural value chains linking farms to cities are undergoing a “quiet revolution.” Governance to enhance food security in the context of rapid urbanization faces various challenges in the institutional, administrative, and political realms, especially for the informal economy in developing countries. To address the unique challenges of urbanization, policies will need to create enabling environments, promote efficient and inclusive value chains, improve governance, and promote tailored programs. Research gaps that need to be filled include better, updated, and disaggregated data on food security and nutrition, as well as an enhanced understanding of enabling environments.The paper highlights the increasingly relevant issue of rapid urbanization, especially in developing countries, for food security and nutrition, and synthesizes recent research in this area.